Extraction of native agar from Gracillaria sp with ultrasonic acceleration at low temperature - Uju Uju; Joko Santoso; Wahyu Ramadhan; Muhammad Fakhri Abrory (Jurnal Pengolahan Hasil Perikanan Indonesia, 2018)
Gracilaria sp. is a potential agar-producing seaweed. The agar is conventially extracted at high temperature (80-100°C) for 2-3 hours, requiring a lot of energy.  Ultrasonication-assisted extraction methodremoves the requirement of high temperatures and shortening the extraction time, thus reduces the energy cost during extraction process.  This study was aimed to determine the effects of temperatures (50 and 60°C) and times (45 and 60 minutes) of ultrasonication on the yield and properties of theproduced agar. Energy efficiency was also calculated based on the ratio of energy required with the amount of agar produced. The ultrasonication significantly increased the yield and energy efficiency. The selected treatment was the extraction with temperature 60°C for 60 minutes producing agar with thee yield of 12.45%, viscosity of 35.8 cP, white degree of 50.96%, moisture content of 12.59%, ash content of 7.07%, sulfate content 3.67% and gel strength 108.03 g/cm2. Agar produced with the selected treatment was grouped as native agar with low gel strength.